Reading the waste land in the age of anxiety: Fragmentation, cultural dislocation, power, and violence in contemporary perspective - Saleh, Shoeb; Alomari, Mohammad Ahmad Shehadeh; Elsayed Hassan, Eid Awad Abd; Sagir Khan, Aayesha; Zaher, Ashraf M (Research Journal in Advanced Humanities, 2026)
This manuscript argues that T. S. Eliot’s The Waste Land remains one of the most illuminating poetic anatomies of anxiety because it does not merely describe crisis; it formalizes it. The poem’s abrupt shifts of speaker, place, register, quotation, and language do not function as ornamented modernist difficulty alone. They enact the lived temporality of fractured attention, deferred mourning, historical overload, and cultural dislocation. By reading the poem through modernist criticism, trauma theory, affect studies, urban theory, media theory, and contemporary discussions of digital precarity, climate unease, disinformation, and social fragmentation, this study shows how The Waste Land continues to speak powerfully to the present. Its “heap of broken images” is not simply a figure for postwar ruin; it is also a durable model of what it feels like to inhabit institutions, mediascapes, and economies that disrupt continuity, weaken shared meaning, and estrange subjects from place, memory, and one another. The article therefore brings together canonical Eliot scholarship with contemporary interdisciplinary work, including recent studies from the Ianna Journal of Interdisciplinary Studies on mental health, social media, disinformation, climate perception, cultural resilience, and ethical digital life. The central claim is that The Waste Land should be read today not as an artifact safely enclosed within the crisis of 1922, but as a continuing diagnostic poem whose form anticipates contemporary structures of anxious life: accelerated perception, intimate depletion, mediated violence, ecological dread, and the difficulty of imagining collective repair.